Comparison of Efficacy between Propranolol and Steroid for Infantile Hemangioma (Medical Forum Monthly, 2024)
Objective: To determine the efficacy and safety of propranolol compared with steroid as a first-line treatment for Infantile Hemangioma.Study Design: A Randomized Control Trial study.Place and Duration of Study: This study was conducted at the Department of Peads Surgery, Children Hospital, Multan and Department of Peads Surgery, NMU, Multan April 2014 to April 2017.Materials and Methods: After obtaining ethical permission from hospital ethical committee and informed consent from parents of participants. A total of 84 patients were included in trial through non probability consecutive sampling technique, and divided into two equal groups. After completion of information and data collection, analyses was done by using SPSS software, for continuous variables mean ± SD like age, size of hemangioma, weight, BMI and surface area was calculated. Frequencies and percentages were calculated for categorical variables like gender, color of hemangioma. T test and chi square were used to check difference in both groups. P value less than or equal to 0.05 was considered as significant.Results: Overall, 84 patients were included in this study, both genders. The study group was further divided into two equal groups, 50% (n=42) in each. Mean volume, surface area and height of lesion was smaller in steroid group but, the difference was statistically insignificant p=0.801, p=0.479 and p=0.402 respectively.Conclusion: Results of our study revealed that therapeutically propranolol is not inferior to steroids in treatment of infantile hemangioma.